Optimal groundwater extraction under uncertainty: resilience versus economic payoffs - Katic, Pamela G.; Grafton, R. Quentin (Elsevier, 2011)
This paper evaluates the trade-off between resilience and economic payoffs in terms of groundwater extraction where there is a risk of an irreversible and catastrophic event. A dynamic and spatial model is developed that incorporates a stochastic recharge process and the risk of an irreversible catastrophic event (such as saltwater intrusion) that arises when hydraulic heads fall below a given threshold. The results show that if the threshold is uncertain then controlling both the rate and depth of extraction can generate a higher economic return and a lower probability of crossing the threshold than only controlling the rate of extraction. This occurs even if the extraction rate is set optimally and is less than the extraction rate than when two forms of control are used. The model and ndings provide an applied framework to understand and to quantify where there might be 'win-win' outcomes, and trade-offs between economic payoffs and resilience in terms of groundwater extraction.